Qualified Audit Reports: Their Impact on Investment Decisions. - Firth, Michael (The Accounting Review, 1978)
ABSTRACT: The research involved measuring the information content of qualified audit reports on published accounts. The market model was used to measure the abnormal returns associated with various "types" of qualification. It was found that some types of audit qualification had a significant impact on investment decisions while others had very little. There was found to be no relationship between the accounting firm qualifying the accounts and the abnormal returns. The findings suggest that more information on the nature of the audit qualifications should be given.